On Angular Limits of Normal Meromorphic Functions: A Geometric Aspect. (20th January 2014) - Pavicevic, Zarko
Abstract : We will prove the assertions which give necessary and sufficient conditions for a normal meromorphic function on the open unit disk to have an angular limit. The results obtained show that the conditions from the classical Lindelöf theorem, as well as the theorems of Lehto and Virtanen and Bagemihl and Seidel, concerning angular limit values of meromorphic functions, can be weakened.